Effects of Roxadustat on Erythropoietin Production in the Rat Body - Yukiko Yasuoka; Yuichiro Izumi; Takashi Fukuyama; Haruki Omiya; Truyen D. Pham; Hideki Inoue; Tomomi Oshima; Taiga Yamazaki; Takayuki Uematsu; Noritada Kobayashi; Yoshitaka Shimada; Yasushi Nagaba; et al. (Molecules, 2022)
Anemia is a major complication of chronic renal failure. To treat this anemia, prolylhydroxylase domain enzyme (PHD) inhibitors as well as erythropoiesis-stimulating agents (ESAs) have been used. Although PHD inhibitors rapidly stimulate erythropoietin (Epo) production, the precise sites of Epo production following the administration of these drugs have not been identified. We developed a novel method for the detection of the Epo protein that employs deglycosylation-coupled Western blotting. With protein deglycosylation, tissue Epo contents can be quantified over an extremely wide range. Using this method, we examined the effects of the PHD inhibitor, Roxadustat (ROX), and severe hypoxia on Epo production in various tissues in rats. We observed that ROX increased Epo mRNA expression in both the kidneys and liver. However, Epo protein was detected in the kidneys but not in the liver. Epo protein was also detected in the salivary glands, spleen, epididymis and ovaries. However, both PHD inhibitors (ROX) and severe hypoxia increased the Epo protein abundance only in the kidneys. These data show that, while Epo is produced in many tissues, PHD inhibitors as well as severe hypoxia regulate Epo production only in the kidneys.